THE ROLE OF APPLICATION-BASED BASIC LIFE SUPPORT FOR NON-HEALTHCARE PROVIDERS DURING COVID-19 PANDEMIC - Mayang Indah Lestari; Veny Larasati; Noer Rahmat Lubis; Rafif Shidq; Andre Saputra; Stevanus E. Handrawan (Fakultas Kedokteran Universitas Sriwijaya, 2021)
The Coronavirus Disease (COVID-19) pandemic has forced us to make significant changes in teaching and learning activities, including restrictions on face-to-face meetings. However, the process of science transfer can continue with the support of innovation and technological advances. Cardiac arrest can occur anytime and anywhere, including at home, in public facilities, and the workplace. The incidence of cardiac arrest at work increases over time. Through this community, service activity developed the innovation application of Basic Life Support to educate non-health workers. This application contains seven types of educational videos: What is Cardiac Arrest?, Why Basic Life Support Is Important?, Basic Life Support Steps, External Cardiac Massage, Recognize Automated External Defibrillator, and Steps of using Automated External Defibrillator, and Recovery Position.